A year of living distantly: global trends in the use of stay-at-home orders over the first 12 months of the COVID-19 pandemic. Issue 6 (12th October 2021) - Phillips, Toby; Zhang, Yuxi; Petherick, Anna
Abstract : During the first year of the COVID-19 pandemic, non-pharmaceutical interventions (NPIs) were the main pillar of defence to protect human society against the virus. While a variety of modelling studies try to quantify the effects of NPIs, this paper investigates when and how national and subnational governments have taken actions. We observe longitudinal changes in the global pattern of policymaking to combat the COVID-19 pandemic, with a particular focus on stay-at-home orders. Drawing on data from the Oxford COVID-19 Government Response Tracker, we show several important trends. First, while national governments exhibited a strong alignment in policy settings initially in March and April 2020, their cross-country policy heterogeneity has grown since May 2020, although countries within global regions continue to display similarities in their approaches. Second, most governments that have implemented multiple stay-at-home orders over the course of the pandemic have become less sensitive to case levels (insofar as they implement subsequent restrictions at progressively higher case levels), apart from a small number of contrast cases which have mostly eliminated domestic community transmission. Third, pandemic policies are increasingly specific to subnational levels, and there is often significant heterogeneity with regard to policy approaches even within the same country.